Quetiapine and Wolff-Parkinson-White Syndrome - Chen, Michael; Gomaa, Hassaan; Cortez-Resendiz, Alonso; Martin, Christopher; Francis, Andrew; Bellon, Alfredo (Case Reports in Psychiatry, 2020)
Quetiapine is occasionally associated with cardiovascular adverse effects such as QTc prolongation. QTc prolongation is a side effect that requires monitoring in order to avoid more serious cardiac complications. One particular understudied area is the potential for antipsychotics to elicit electroconduction abnormalities in patients with Wolff-Parkinson-White (WPW) Syndrome. In the present report, we describe a case of quetiapine overdose in a patient with WPW.